Critical meta-analysis of problem-solving serious games: Clear signs of pedagogists' disengagement and over-optimistic expectations - Morteza Rezaei-Zadeh; Raazieh Mohagheghiaan; Mojtaba Vahidi-Asl (Serious Games Society, 2023)
Problem-solving is placed at top of the ten most important life skills recommended by World Economic Forum. Serious game has been one of the dominant tools for educating people in different subjects over the last 10 years. This study aims to critically analyse previous empirical studies conducted on Problem-Solving Serious Games (PSSG). Using Constant Comparative Method (CCM) framework, 737 studies in this area are listed; and after applying several filters, 36 studies are refined and finally chosen. The analysis shows that serious games not alone improve people's problem-solving ability, it also positively impacts on their problem-solving motivation, problem-solving measurement ability, critical thinking, and learning attitude. However, there is a lack of pedagogists' engagement with PSSG studies. As a result, those studies suffered from lack of educational rationale behind and lack of right direction in choosing their participants, research methods, focus, genre, and expected outputs. Theoretical and practical implications of this critical analysis are outlined at the end of this paper, shedding light on the future directions of PSSG studies. the main conclusions of this study are as following: 1. An inter-disciplinary approach led by pedagogists is needed to design, develop, and examine PSSGs effectively. 2. The over-optimistic viewpoint about serious games in general and PSSGs in specific should be moderated by looking more closely at the negative marginal and side effects of implementing these games on gamers.